Bioinspired Spiky Peroxidase‐Mimics for Localized Bacterial Capture and Synergistic Catalytic Sterilization. Issue 8 (21st January 2021) - Yang, Ye; Wu, Xizheng; Ma, Lang; He, Chao; Cao, Sujiao; Long, Yanping; Huang, Jianbo; Rodriguez, Raul D.; Cheng, Chong; Zhao, Changsheng; Qiu, Li
Abstract: Besides the pandemic caused by the coronavirus outbreak, many other pathogenic microbes also pose a devastating threat to human health, for instance, pathogenic bacteria. Due to the lack of broad‐spectrum antibiotics, it is urgent to develop nonantibiotic strategies to fight bacteria. Herein, inspired by the localized "capture and killing" action of bacteriophages, a virus‐like peroxidase‐mimic (V‐POD‐M) is synthesized for efficient bacterial capture (mesoporous spiky structures) and synergistic catalytic sterilization (metal–organic‐framework‐derived catalytic core). Experimental and theoretical calculations show that the active compound, MoO3, can serve as a peroxo‐complex‐intermediate to reduce the free energy for catalyzing H2 O2, which mainly benefits the generation of OH radicals. The unique virus‐like spikes endow the V‐POD‐M with fast bacterial capture and killing abilities (nearly 100% at 16 µg mL –1 ). Furthermore, the in vivo experiments show that V‐POD‐M possesses similar disinfection treatment and wound skin recovery efficiencies to vancomycin. It is suggested that this inexpensive, durable, and highly reactive oxygen species (ROS) catalytic active V‐POD‐M provides a promising broad‐spectrum therapy for nonantibiotic disinfection. Abstract : A bioinspired, spiky, and highly catalytic‐active virus‐like peroxidase‐mimic (V‐POD‐M) is synthesized for the localized "capture and killing" eradication of pathogenic bacteria. Experimental and theoretical calculations demonstrate that the V‐POD‐M exhibits strong bacterial interactions and efficient capture, synergistic catalytic sterilization, and similar in vivo disinfection efficiency to that of vancomycin, which provides a promising broad‐spectrum therapy for nonantibiotic disinfection.